Magnitude and Determinants of Postnatal Mothers' Knowledge of Essential Newborn Care at Home in Rural Ethiopia - Getachew, Tamirat; Dheresa, Merga; Eyeberu, Addis; Balis, Bikila; Yadeta, Tesfaye Assebe (Frontiers in Pediatrics, 2022)
Introduction: Globally, nearly, three million children die in the neonatal period. Although there is scant information about rural mothers, the enhancement of mothers' knowledge and skills towards ENC is a vital aspect in the reduction of newborn illness and mortality. Thus, this study aimed to assess the magnitude and determinants of mothers' knowledge of ENC. Methods: A community-based cross-sectional study was conducted among recently delivered women using a multistage sampling method in Chole woreda. Data were collected via face-to-face interviews. A multivariate logistic regression model was used to identify the determinant factors with the level of knowledge. Odds ratios with a 95 % confidence interval was used to describe association and significance was determined at a p-value less than 0.05. Results: Data from 510 mothers were employed for analysis. Overall, 33.5% (95%CI: 29.4%, 37.6%) of the mothers had good knowledge of ENC. Antenatal care visits [AOR: 2.42; 95%CI: (1.50, 3.88)], counseled about ENC during ANC [AOR: 5.71; 95%CI: (2.44, 13.39)], delivery at health institutions [AOR: 2.41; 95%CI: (1.30, 4.46)], religion [AOR 1.99, CI: (1.25, 3.16)] and educational level [AOR= 1.64 95%CI: (1.10, 2.51)] were significantly associated with knowledge of ENC. About 74%, 75%, and 41% of mothers practiced appropriate cord care, breastfeeding, and thermal care, respectively. Conclusion: Three out of ten mothers had a good level of knowledge of ENC. Knowledge gaps identified pertained to cord care, breastfeeding, and thermal care. There is an opportunity to enhance maternal knowledge of ENC through improving access to ANC and institutional delivery.